Insulin resistance may accelerate typical changes in heart function among type 1 diabetes patients, particularly in overweight patients: a preliminary study - Czarnik, Klaudia; Sablik, Zbigniew; Borkowska, Anna; Drożdż, Jarosław; Cypryk, Katarzyna (Frontiers in Endocrinology, 2024)
Introduction Type 1 diabetes (T1D) is a metabolic disease characterized by insulin deficiency and subsequent hyperglycemia. Cardiovascular diseases are the prime cause of mortality and morbidity among patients with T1D. Accumulating metabolic disturbances and accelerated cardiac fibrosis fuel the development of heart dysfunction. As insulin resistance (IR) is a risk factor for the development and worsened course of heart failure, this study aimed to assess its impact on heart function in patients with T1D. Methods Adult participants were recruited prospectively. The inclusion criteria included a diagnosis of T1D. The exclusion criteria were other types of diabetes, symptoms/treatment of heart failure, AST and/or ALT exceeding the upper reference limit by ≥2x, hepatitis, alcoholism, metformin treatment, and pregnancy. The participants underwent a medical interview, physical examination, biochemical test, and echocardiography. Results The mean age in the study group was 38 ± 9.6 years, and the mean diabetes duration was 21.8 ± 11.3 years. The median BMI in the study cohort was 23.39 kg/m2. Patients with IR had significantly lower mitral E/A ratio and left ventricular and left atrial volume ratio (LVLAVR), higher LV mass index, and presented with altered mitral annular velocities. Conclusions IR seems to accelerate the pattern of typical changes in heart function among patients with T1D, especially in the overweight subgroup.